Hak Penguasaan Negara Terhadap Sumber Daya Alam Dan Implikasinya Terhadap Bentuk Pengusahaan Pertambangan - Hayati, Tri (UI Scholars Hub, 2019)
Granting mining licenses brings various negative impacts in various aspects. In addition to the environmental damage that must have been caused, it also caused a lot of leakage in the revenue of state finances that should have been received by the State. Permits should be a controlling instrument in mining operations, so that they are in accordance with the philosophical meaning as mandated by Article 33 paragraph (3) of the 1945 Constitution. The meaning contained in the Article is the principle of